Karakteristik Kimiawi Kulit Pai Substitusi Tepung Pisang Jantan Termodifikasi Fisik - Widiana, Dea Rizki; Zukryandry, Zukryandry; Puspitasari, Kiki; Dalimunthe, Nathasa Khalida (Universitas Ahmad Dahlan, 2025)
Banana (Musa spp.) is one of the leading local food commodities in Lampung with high productivity, but it has a relatively short shelf life because it is classified as a climacteric commodity. One of the developments to overcome this issue is by processing bananas into physically modified banana flour as a form of food diversification. The modified banana flour can then be further processed into various food products as an alternative to wheat flour, for example the pie crust product. This study aims to determine the chemical characteristics of the best pie crusts made by substituting physically modified banana flour from the previous study. The pie crusts produced using the substitution of physically modified banana flour showed the best treatment with a substitution ratio of 30:70 (banana flour: wheat flour). The resulting pie crusts were tested for proximate composition and showed moisture content of 4.96%, ash content of 0.54%, fiber content of 3.03%, fat content of 9.67%, protein content of 4.85%, and carbohydrate content by difference of 76.95%. This product meets the SNI (Indonesian National Standard) moisture content standard for biscuits. It is expected that this research will provide useful information and opportunities for the development of diversified local banana-based food products in Lampung.